25.6k views
0 votes
Equation -2x - 23 = 13x + 22 with explanation plz

User Skibulk
by
5.2k points

1 Answer

3 votes

Answer:

x = -3

Explanation:

first, take out the x on the right side and move it to the left side (subtract the 13x from 13x and subtract 13x from -2x). then amove 23 from the left side to the right side (add 23 to 23 and add 23 to 22). the equation should be -15x = 45 now. divide -15 from both sides and you should get x = -3!

i hope this helps you!

User Osynavets
by
4.6k points